Implementation of Greenhouse Gas Reduction in the Unmanned Vehicles Industry Using Composite Material - Handoko Subawi (ITB Journal Publisher, LPPM ITB, 2021)
The study purposes to assess the environmental aspect of the process technology of medium-altitude long-endurance unmanned vehicles. The potential impact is estimated using the impact characterization value parameter which is calculated using the SimaPro method. Further the normalization value is obtained using the normalization factor referring to the international reference life-cycle data system (ILCD). Based on the study, the parameters of climate change and freshwater ecotoxicity are the two dominant parameters among the ten categories of environmental impacts studied. The source of this impact comes from the use of diesel fuel to operate the boiler and the use of chemicals for the surface treatment process of components made of aluminum metal. The production capacity of the unmanned vehicle under study is six vehicles per year, with an airframe weight of 431 kg per vehicle, excluding the propeller system and avionics. When compared with the design of similar vehicles made of metal, the potential for reducing climate change pollution that can be achieved is 302,153 kg CO2 eq./kg of product, while the potential for reducing freshwater ecotoxicity is 187,837 kg 1,4-dichlorobenzene eq./kg of product.